Respostas
respondido por:
0
Espero ter ajudado!!! Bons estudos!!!
Anexos:
alineandrebento:
Obg flor
respondido por:
0
Tens que resolver pela fórmula resolvente x=-b+-√b²-4ac tudo a dividir por 2.a
x²-6x+7=0
a=1; b=-6, c=7
x= -(-6)+-√(-6)²-4.1.7/2.1
x= 6+-√36-28/2
x= 6+-√8/2
x= 6-√8/2 ou x= 6√8/2
x= 3-√8 ou x= 3√8
x²-6x+7=0
a=1; b=-6, c=7
x= -(-6)+-√(-6)²-4.1.7/2.1
x= 6+-√36-28/2
x= 6+-√8/2
x= 6-√8/2 ou x= 6√8/2
x= 3-√8 ou x= 3√8
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás